2001
DOI: 10.1086/321096
|View full text |Cite
|
Sign up to set email alerts
|

Speckle Interferometry of New and Problem [ITAL]HIPPARCOS[/ITAL][ITAL]Hipparcos[/ITAL] Binaries. II. Observations Obtained in 1998–1999 from M[CLC]c[/CLC]Donald Observatory

Abstract: The Hipparcos satellite made measurements of over 9734 known double stars, 3406 new double stars, and 11,687 unresolved but possible double stars. The high angular resolution a †orded by speckle interferometry makes it an efficient means to conÐrm these systems from the ground, which were Ðrst discovered from space. Because of its coverage of a di †erent region of angular separationÈmagnitude di †erence (o-*m) space, speckle interferometry also holds promise to ascertain the duplicity of the unresolved Hipparc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…The Hipparcos observations of o Per revealed the presence of a visual companion at a separation of 1.02 and with a magnitude difference of 2.91 mag. Speckle interferometry by Mason et al (2001) confirmed this detection. If this visual companion is physically related to o Per, and if we assume it to be a main-sequence star, its magnitude suggests a spectral type of ∼B4 and an estimated mass of ∼4−6 M .…”
Section: The B1 III Star O Persupporting
confidence: 56%
“…The Hipparcos observations of o Per revealed the presence of a visual companion at a separation of 1.02 and with a magnitude difference of 2.91 mag. Speckle interferometry by Mason et al (2001) confirmed this detection. If this visual companion is physically related to o Per, and if we assume it to be a main-sequence star, its magnitude suggests a spectral type of ∼B4 and an estimated mass of ∼4−6 M .…”
Section: The B1 III Star O Persupporting
confidence: 56%
“…In their survey of the Solar neighbourhood, Nordström et al (2004) reported [Fe/H] = +0.33 for this star. Mason et al (2001) observed it twice using speckle-interferometry but found no evidence for multiplicity. However, the night-averaged CCF shows a slight and systematic bump on the left side of the main peak which could be related to the presence of a secondary component.…”
Section: Hd 68725 -Hip 40361mentioning
confidence: 99%
“…We identified 16 spectroscopic binaries (SB) in our sample of 81 solar twins by analyzing their radial velocities; some of these stars are reported as binaries by Tokovinin (2014a,b), Mason et al (2001), Baron et al (2015). We did not find previous reports of multiplicity for the stars HIP 30037, HIP 62039 and HIP 64673 in the literature.…”
Section: Binary Starsmentioning
confidence: 96%